Classic Yoga : A New Approach to Fitness and Relaxation : A Three-Part Foundation Course - Lalvani, Vimla (London Hamlyn, an Imprint of Reed Consumer Books Ltd., 1996)
This beginner's guide to yoga is designed to de-mystify the ancient science of movement and bring it into the 1990s. The introduction outlines the principles and history of yoga and is followed by simple instructions on breathing techniques.
Include Color Illustrations.
A New Approach to Fitness and Relaxation.
Keywords: Hatha yoga -- Physical fitness -- Relaxation -- Yoga